The thickness of erector spinae muscles can be easily measured by computed tomography for the assessment of physical activity: An observational study. Issue 38 (23rd September 2022) - Shimoda, Masafumi; Takao, Satoshi; Sugajima, Yasushi; Tanaka, Yoshiaki; Morimoto, Kozo; Yoshida, Naoyuki; Yoshimori, Kozo; Ohta, Ken; Senjyu, Hideaki
Abstract : The loss of muscle mass and changes in muscle composition are important factors for assessing skeletal muscle dysfunction. The cross-sectional area (CSA) of muscle is usually used to assess skeletal muscle function. However, the CSA of skeletal muscle can be difficult for clinicians to measure because a specific 3D image analysis system for computed tomography (CT) scans is needed. Therefore, we conducted a study to develop a new method of easily assessing physical activity, in which the thickness of the erector spinae muscles (ESMT ) was measured by CT, and to compare ESMT to the CSA of the erector spinae muscles (ESMCSA ) in patients with nontuberculous mycobacteria (NTM) pulmonary infections who underwent surgery after some preoperative examinations, such as laboratory tests, chest CT scans, spirometry, and 6-minute walk tests (6MWT). We retrospectively studied adult patients with NTM pulmonary infections who underwent a lobectomy at Fukujuji Hospital from April 2010 to March 2016. We assessed the correlations between ESMT and different variables, including ESMCSA . Sixty-one patients with NTM pulmonary infections were included. The median ESMT and ESMCSA were 1371 mm 2 (IQR 1178–1784 mm 2 ) and 28.5 mm (IQR 25.4–31.7 mm), respectively, and a very strong linear correlation was observed between ESMT and ESMCSA ( R  = 0.858, P  < .001). ESMT and ESMCSA were positively associated with body weight (ESMT : R  = 0.540, P  < .001, ESMCSA : R  = 0.714, P  < .001), body mass index (ESMT : R  = 0.421, P  < .001, ESMCSA : R  = 0.560, P  < .001), the 6MWT value (ESMT : R  = 0.413, P  = .040, ESMCSA : R  = 0.503, P  = .010), vital capacity (ESMT : R  = 0.527, P  < .001, ESMCSA : R  = 0.577, P  < .001), and the forced expiratory volume in 1 second (ESMT : R  = 0.460, P  < .001, ESMCSA : R  = 0.532, P  < .001). We demonstrated that compared to ESMCSA, ESMT is easily measured by CT and can be a useful parameter for clinically evaluating physical activity. Furthermore, ESMT and ESMCSA were related to physical activity, as measured by the 6MWT and spirometry.